2009
DOI: 10.1021/jf901801z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glyphosate−Boron Application on Seed Composition and Nitrogen Metabolism in Glyphosate-Resistant Soybean

Abstract: The objective of this study was to evaluate the effects of foliar application of glyphosate (Gly) alone, boron (B) alone, and Gly-B combined on seed composition and nitrogen metabolism in glyphosate-resistant soybean (Glycine max (L.) Merr.). No Gly and no B application plants were used as control (C). Results showed that Gly, Gly-B, or B applications increased protein, oleic acid, and total amino acid concentrations in seed. However, oil and linolenic acid concentrations decreased under those treatments compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 43 publications
6
43
0
Order By: Relevance
“…Previous research showed that there was a positive relationship between soil B and seed protein and oleic acid, suggesting an indirect role of B in seed composition [33]. Other research showed that foliar B application increased soybean seed protein and oleic acid concentrations [32,34].…”
Section: Effect Of Foliar Application With B On Amino Acids Compositimentioning
confidence: 96%
“…Previous research showed that there was a positive relationship between soil B and seed protein and oleic acid, suggesting an indirect role of B in seed composition [33]. Other research showed that foliar B application increased soybean seed protein and oleic acid concentrations [32,34].…”
Section: Effect Of Foliar Application With B On Amino Acids Compositimentioning
confidence: 96%
“…The source of lighting was a mixture of natural light, bulb light (60 W), cool white (250 W). To avoid differences in the day-length between the two experiments, the two experiments were conducted simultaneously at the same time and during the normal growing season (from April to September) for the Early Soybean Production System in the midsouth USA, and this is to be consistent with the normal photoperiod for soybean growth [10].…”
Section: Methodsmentioning
confidence: 99%
“…Samples were read at 420 nm using a Beckman Coulter DU 800 spectrophotometer (Fullerton, California). Boron analysis in soil was conducted using Inductively Coupled Plasma spectrometry (ICP) using Thermo Elemental, Thermo Jarrell-Ash model 61E ICP, USA [10]. C isotopes was determined using about 0.9 mg of ground seeds.…”
Section: Boron Determinationmentioning
confidence: 99%
See 2 more Smart Citations